Bridging the Divide: Integrative Curriculum Management in Islamic Boarding Schools - Imelia Sahda Salsabilla; Baqiyatush Sholihah; M. Rikza Chamami; Abdul Rofik; Umi Hani; Zarkasi Zarkasi (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2026)
This study investigates the implementation of integrative curriculum management in Islamic boarding schools to bridge the dichotomy between religious and general education. It focuses on how curriculum integration is planned, implemented, and evaluated, as well as its impact on students’ competencies. A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and document analysis involving six key informants. The findings reveal that integrative curriculum management is systematically carried out through synchronized planning, contextual learning practices, and continuous evaluation. This approach significantly strengthens students’ holistic competencies, including religious understanding, academic achievement, critical thinking, and moral character. The success of implementation is strongly influenced by leadership commitment, institutional culture, and collaborative teaching practices. In addition, adaptive strategies are proven effective in addressing resistance to change and maintaining curriculum relevance in the face of global challenges. However, inconsistencies at the instructional level indicate that integration has not been fully internalized by all educators. This study contributes an empirical model of integrative curriculum management in pesantren, offering a practical framework for educational reform that is both contextually grounded and globally relevant. Further research across diverse settings is recommended to enhance external validity.